Beyond Victims: Motherhood and Human Rights - Payne, Anne Maree (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This article discusses specific cases in which women’s reproductive capacity and maternal roles have resulted in human rights violation. It finds that in the context of genocide, women and girls may be specifically targeted because of their reproductive capacity; in assimilationist contexts, mothers may be targeted because of perceptions about their gendered role in the transmission of culture; and women’s gendered role of caring for children and the elderly may also increase their vulnerability to harm in some contexts. The role of mothers’ groups who work for justice in the aftermath of human rights violations is also discussed. Such activism falls within the range of socially acceptable behaviour by mothers, but some dismiss it as innately conservative and limited. It is important to recognize the range of roles that women (and mothers) undertake in the context of human rights violation, extending beyond that of victim, to ensure that women’s agency and activism are recognized.